2022
DOI: 10.3390/su14031436
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Harvest Practices and Varietal Preferences of Tomato in Ghana

Abstract: Tailored interventions in the tomato sector require current information on production and marketing systems along with the constraints faced by the stakeholders. We conducted this study to understand the current production practices, stakeholders’ varietal preferences, tomato market trends, and challenges along the crop’s value chains. A multistage sampling method coupled with a random walk was used to identify survey locations and identify 180 respondents across seven regions in Ghana. The study showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(33 reference statements)
3
8
1
Order By: Relevance
“…Our findings also differ with those of Ochilo et al [5] who opined that the tomato varieties grown by the farmers was determined by the cost of seeds. Additionally, our findings contradict those of Melomey et al [42] in Ghana who observed that most farmers choose varieties based on adaptability as opposed to market preference.…”
Section: Tomato Varieties Grown Reason For the Variety Grown And Sour...contrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings also differ with those of Ochilo et al [5] who opined that the tomato varieties grown by the farmers was determined by the cost of seeds. Additionally, our findings contradict those of Melomey et al [42] in Ghana who observed that most farmers choose varieties based on adaptability as opposed to market preference.…”
Section: Tomato Varieties Grown Reason For the Variety Grown And Sour...contrasting
confidence: 99%
“…The finding on the level of education among tomato farmers differs with those reported by Ddamulira [48] in Uganda where majority (52.2%) of tomato farmers had attained secondary education with 29% having attained only primary education level. However, our finding corroborates with those of Melomey et al [42] where tomato farmers who had primary education were 19% and secondary education were 58%. Education level of farmers may influence how the farmer follows proper agronomic practices of tomato production such as application of fertilizer, insecticide and fungicide [49].…”
Section: Gender Age Education Level and Tomato Farming Historysupporting
confidence: 92%
See 2 more Smart Citations
“…This is crucial in considering the breeding objectives whether for industrial processing or home consumption. In Ghana, tomato production is either for processing into paste or direct consumption by consumers who purchase from the open market [51]. A demand-led programme should consider value chain analysis and innovation systems that involve all the actors in the value chain of the crop.…”
Section: Demand-led Principles and Approaches For Tomato Breedingmentioning
confidence: 99%